The Representation of Syntactic Meaning as the Environmental Symbolic Reality in the Novel The Lorax by Dr. Seuss - Nur Ari Ramadhan; Jepri (Prologue: Journal on Language and Literature, 2023)
The research discusses about the syntactic meaning in the syntax category that is specifically included in the form of ecolexicon, representing the environmental symbolic reality. The syntax categories are focused on elaborating the phrases and sentences consisting of the specific ecolexicon: biotic and abiotic references. This research is focused on the syntactic meaning that represents the environmental symbolic reality found in The Lorax novel by Dr. Seuss. There are two objectives for the purpose of this research, 1) to identify the forms of the syntactic meaning of the environment in the novel The Lorax by Dr. Seuss and 2) to describe the forms of syntactic meaning representing the environmental symbolic reality in The Lorax by Dr. Seuss. This research uses the Ecolinguistics theory from Fill & Mühlhäusler. The researcher uses a qualitative method explaining descriptively based on this research using a library study as a reference. The research's result found ten forms of syntactic meaning divided into six phrases with 14 data and four sentences with 19 data. Then, the representation of the environmental symbolic reality consists of Waste Disposal and Pollution with 11 data, Endangered Species 10 data, Climate Change 1 data, Water 1 data, and Deforestation 10 data.